The Routledge companion to philosophy of psychology - Robins, Sarah; Symons, John; Calvo, Paco (Routledge Philosophy Companions, 2020)
The Routledge Companion to Philosophy of Psychology, Second Edition is an invaluable guide and major reference source to the key topics, problems, concepts, and debates in philosophy of psychology and is the first companion of its kind. A team of renowned international contributors provide forty-eight chapters, organized into six clear parts: Historical background to philosophy of psychology Psychological explanation Cognition and representation The biological basis of psychology Perceptual experience Personhood. The Companion covers key topics, such as the origins of experimental psychology; folk psychology; behaviorism and functionalism; philosophy, psychology and neuroscience; the language of thought, modularity, nativism, and representational theories of mind; consciousness and the senses; dreams, emotion, and temporality; personal identity; and the philosophy of psychopathology. For the second edition, six new chapters have been added to address the following important topics: belief and representation in nonhuman animals; prediction error minimization; contemporary neuroscience; plant neurobiology; epistemic judgment; and group cognition. Essential reading for all students of philosophy of mind, science, and psychology, The Routledge Companion to Philosophy of Psychology will also be of interest to anyone studying psychology and its related disciplines